The Association Between Folate and Alzheimer's Disease: A Systematic Review and Meta-Analysis - Zhang, Xiaohong; Bao, Guangyi; Liu, Debiao; Yang, Yu; Li, Xuezhi; Cai, Gaomei; Liu, Yan; Wu, Yili (Frontiers in Neuroscience, 2021)
Alzheimer's disease (AD) is the most common type of neurodegenerative disease leading to dementia in the elderly. Increasing evidence indicates that folate plays an important role in the pathogenesis of AD. To investigate the role of folate deficiency/possible deficiency in the risk of AD and the benefical effect of sufficient folate intake on the prevention of AD, a systematic review and meta-analysis were performed. The Web of Science, PubMed, CENTRAL, EBSCO, CNKI, CQVIP, and Wanfang databases were searched. The analysis of cross-sectional studies showed that the standardized mean difference (SMD) was −0.60 (95% confidence interval (CI): −0.65, −0.55), indicating that plasma/serum folate level is lower in AD patients than that in controls. Moreover, the combined odds ratio (OR) of case-control studies was 0.96 (95% CI: 0.93, 0.99), while the combined ORs were 0.86 (95% CI: 0.46, 1.26) and 1.94 (95% CI: 1.02, 2.86) in populations with normal levels of folate (≥13.5 nmol/L) and folate deficiency/possible deficiency (<13.5 nmol/L), respectively. In addition, the risk ratio (RR) of the cohort studies was 1.88 (95% CI: 1.20, 2.57) in populations with folate deficiency/possible deficiency. Furthermore, when the intake of folate was equal to or higher than the recommended daily allowance, the combined RR and hazard ratio (HR) were 0.44 (95% CI: 0.18, 0.71) and 0.76 (95% CI: 0.52, 0.99), respectively. These results indicate that folate deficiency/possible deficiency increases the risk for AD, while sufficient intake of folate is a protective factor against AD.